POLA KOMUNIKASI PEMIMPIN DALAM MEWUJUDKAN ORGANISASI INKLUSIF PADA UKM BELA DIRI UIN SUNAN AMPEL SURABAYA - Ariza Qurrata A'yun; ENDAH S (Sintesa, 2026)
Leader communication patterns are a crucial factor in creating an inclusive organization, particularly in environments with diverse member backgrounds. This study aims to analyze leader communication patterns in realizing an inclusive organization within the Self-Defense Student Activity Unit (UKM) of UIN Sunan Ampel Surabaya, which houses four different pencak silat schools. This study employed a qualitative approach with descriptive methods, with data collection techniques through in-depth interviews, observation, and documentation during joint training activities. The results indicate that the Y communication pattern according to Joseph A. DeVito is implemented by leaders as the primary liaison between members and between schools. This pattern allows for a focused flow of information while also opening up space for member participation. In addition, the application of Bernard M. Bass's Transformational Leadership Theory is evident through the development of a shared vision, providing motivation, open communication, and attention to the individual needs of members. This contributes to creating an inclusive organizational environment, minimizing conflict, and strengthening solidarity     and  cooperation.  From  an  Islamic  da'wah  perspective,  these communication practices align with the values of brotherhood, justice, and deliberation in social life. Thus, the leader's communication patterns play a strategic role in shaping an adaptive, harmonious organization capable of constructively managing diversity within the Self-Defense Student Activity Unit (UKM) at UIN Sunan Ampel Surabaya. Keywords: Communication Patterns, Transformational Leadership, Inclusive Organization, Self-Defense Student Activity Unit, Organizational Communication.